Online search and activities of parents of children with ADHD: a qualitative study - Marie Bringer; Sylvain Bodard; Ana Moscoso; Anne Revah-Levy; Diane Purper-Ouakil; Eric Acquaviva; Richard Delorme; Benjamin Landman; Jordan Sibeoni (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Parents’ perceptions of their child’s mental health play a crucial role in their decision to seek mental health services. Additionally, mental health literacy, which includes knowledge about mental health disorders, is essential for identifying, managing, and preventing mental health problems. Online health information searches are a vital resource for parents of children with attention deficit hyperactivity disorder (ADHD)– one of the most common neurodevelopmental disorders– as they provide emotional support and information on risk factors, treatments, and prognosis. However, while online resources are widely used, little is known about how parents navigate, interpret, and integrate this information into their care decisions. This study explored parents’ lived experiences of seeking ADHD-related information online, examining how these searches shape their perceptions, decision-making, and interactions with healthcare professionals. Method This qualitative study followed the Inductive Process to analyze the Structure of lived Experience (IPSE) approach. Twenty parents of children with ADHD were recruited using a purposive sampling strategy, and data were collected through semi-structured interviews until saturation was reached. Data analysis was conducted using a descriptive and structuring procedure to identify key experiential themes. Results Data analysis produced three central experiential axes: [1] Internet and the care pathway; [2] Internet knowledge and its supporting role; and [3] Internet and discordant discourse on ADHD between health professionals. Most parents reported using social networks as a crucial source of support, guidance, and mutual aid. Specifically, online parent groups helped them navigate obstacles in the care pathway, manage conflicting perspectives on ADHD, and alleviate feelings of guilt. Conclusion Healthcare professionals and stakeholders should consider the impact of web-based resources on parental decision-making and work towards improving the accessibility and reliability of online health information.